Papua New Guinea : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 2000)
This report describes Papua New Guinea's recent economic developments by assessing its output and price developments. The paper discusses the central government finances, tax and expenditure policies, the public sector reform program, and pension funds. The study also analyzes the institutional and operational aspects of the Bank of Papua New Guinea under the central banking act; instruments of monetary policy; and monetary policy and developments. The report reviews the nature and operation of the foreign exchange market, developments in the balance of payments, and external debt trends.